Effect of commercial starter cultures and native yeasts on ochratoxin a production by aspergillus westerdijkiae and penicillium nordicum in meat products - Meftah, Sana (2016)
Processed meat products are of worldwide importance and, because of their intrinsic factors as well as the processing methods, they are highly prone to fungal and mycotoxin contamination. Ochratoxin A (OTA) is the most significant mycotoxin in processed meat products. Penicillium nordicum is considered to be responsible for OTA contamination of meat products, as it is highly adapted to salt and protein-rich matrices and is moderately psycrotrophic. However, another OTA-producing fungus, Aspergillus westerdijkiae, adapted to carbon-rich matrices such as cereals and coffee beans, has been recently associated with high levels of OTA in meat products. Several Lactic Acid Bacteria (LAB) and yeasts have been tested as biocontrol agents against P. nordicum growth and OTA production in meat products, with promising results, but none of the studies have considered A. westerdijkiae. The aim of this work was to evaluate in vitro the effect of a commercial starter culture used in sausage fermentation and four yeasts isolated from dry-cured sausage on these two OTA-producing fungi, both in terms of fungal growth and of OTA production, using different meat-based culture media as model systems. The mechanisms underlying the observed effect were also studied. For this purpose, C. krusei, C. zeylanoides, R. mucilaginosa, R. glutinis, a mix of these yeasts and the starter culture were co-inoculated with P. nordicum and A. westerdijkiae in industrial sausage, traditional sausage, and ham-based media, under conditions of water activity, salt concentration and temperature that mimic real conditions at beginning and end of sausage curing process. Fungal growth was determined by measuring colony diameter, and OTA production was quantified by HPLC-FLD after extraction with methanol. Yeasts where found to inhibit significantly the growth of both fungi. P. nordicum was unable to produce detectable OTA in both sausage-based media under any condition. In ham, yeasts reduced OTA production, while the starter culture significantly increased it. Unexpectedly, OTA production by A. westerdijkiae was significantly stimulated in all media tested by all microorganisms. Matrix has a significant effect on OTA production by P. nordicum, but not by A. westerdijkiae, for which only temperature showed to have effect. By testing the mechanisms of action by which starter culture and C. zeylanoides influenced fungal responses, we were able to determine that direct contact and simultaneous growth of test organisms were the mechanisms more significantly involved in the responses. In conclusion, ochratoxigenic fungi do not all respond to antagonistic microorganisms in the same way. The use of biocontrol agents with the intent of reducing fungal growth and mycotoxin production by one fungus can have unexpected effects on others, thus leading to unforeseen safety problems. Further experiments are recommended to properly understand the reasons behind the different effects of microorganisms, to ensure their safe as biocontrol agents.